2021
DOI: 10.1002/advs.202102550
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Atom Ru Implanted on Co3O4 Nanosheets as Efficient Dual‐Catalyst for Li‐CO2 Batteries

Abstract: Li‐CO 2 battery has attracted extensive attention and research due to its super high theoretical energy density and its ability to fix greenhouse gas CO 2 . However, the slow reaction kinetics during discharge/charge seriously limits its development. Hence, a simple cation exchange strategy is developed to introduce Ru atoms onto a Co 3 O 4 nanosheet array grown on carbon cloth (SA Ru‐Co 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 60 publications
2
57
0
Order By: Relevance
“…The separation of the peaks for the Co element shows that Co exists in PAO‐Co in the form of Co—N (782.5 eV), Co—O (780.5 eV), Co 2+ (780.1 eV), and Co 0 (778.4 eV) (Figure 2c ). [ 23 ] Based on inductively coupled plasma mass spectrometry (ICP‐MS) and XPS analyses, the mass ratio of the total Co element and Co single atoms comprise of 8.49% and 0.71% of the material, respectively. The interaction between Co with N and O, which belongs to the amidoxime group, proves that Co element is bound by the amidoxime group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The separation of the peaks for the Co element shows that Co exists in PAO‐Co in the form of Co—N (782.5 eV), Co—O (780.5 eV), Co 2+ (780.1 eV), and Co 0 (778.4 eV) (Figure 2c ). [ 23 ] Based on inductively coupled plasma mass spectrometry (ICP‐MS) and XPS analyses, the mass ratio of the total Co element and Co single atoms comprise of 8.49% and 0.71% of the material, respectively. The interaction between Co with N and O, which belongs to the amidoxime group, proves that Co element is bound by the amidoxime group.…”
Section: Resultsmentioning
confidence: 99%
“…The result of the XPS analysis revealed that the zero‐valent Co element was transformed into the valent of Co 2+ and Co 3+ , represented by the two satellite peaks at 785.5 and 801.9 eV, respectively (Figure 2d ). [ 23 , 24 ] After using the material for antimicrobial activity assay, the total amount of the Co element is also reduced from 84.9 mg g −1 in the initial material to 41.5 mg g −1 in the used material (Figure S2 , Supporting Information). The Co content decreases because the material cannot completely bind the Co ions owing to the higher binding affinity of the amidoxime group to the uranyl ion than to the Co ion.…”
Section: Resultsmentioning
confidence: 99%
“…Those flake-like discharge products have also been reported in some literature studies and confirmed to be Li 2 CO 3 , indicating the conformal growth mode without the formation of large particles. 13,33,34 The conformal growth of Li 2 CO 3 can be attributed to the high catalytic performance towards PdCu nanoalloys, for that the bulk Li 2 CO 3 have been found in Cu/N-CNF based Li-CO 2 batteries (Fig. S8 †).…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] To conquer these barriers, a lot of effort has been made to explore high-efficiency bifunctional electrochemical catalysts towards both the CO 2 reduction reaction (CRR) and the CO 2 evolution reaction (CER). To date, carbon-based cathodes 5,6 including compounds with transition metal oxides/carbides, [13][14][15] noble metals, 11,13,16 metal-organic frameworks 17,18 and covalent organic frameworks (COFs) 8,19 have achieved a lot of effective and fruitful results in Li-CO 2 batteries. Among all, mono metal catalysts (like Au, Ru and Ir) have been reported to exhibit great catalytic performance toward the reduction and evolution of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[18] More importantly, the electrocatalytic capability of Ru-based catalyst is intrinsically highly versatile by virtue of the vast tunability in electronic structure. [19] Strategies including metal-support interaction (e.g., Ru SA -Co 3 O 4 [20] ), alloying engineering (e.g., RuRh alloy [21] and RuCu alloy [22] ), ligand engineering (e.g., RuP 2 [23] and Ru-organic ligand complex [24] ) were employed for developing Ru-based catalysts with tuned electronic structures, which can not only effectively facilitate reaction kinetics but also modify the reaction mechanism in Li-CO 2 battery. For instance, it was reported that Ru II center in Ru(bpy) 3 Cl 2 complex is able to interact with both CO 2 and Li 2 C 2 O 4 intermediate, thereby delaying carbonate transformation.…”
Section: Introductionmentioning
confidence: 99%